Economic Investigation of Utility Maximization through Mathematical Analysis - Mohajan, Haradhan Kumar; Mohajan, Devajit (Annals of Spiru Haret University. Economic Series, 2024)
In this paper economic predictions among commodity prices and Lagrange multipliers are deliberated, where utility maximization policy is examined with sufficient mathematical investigation. In mathematical economics, utility reflects the propensity of an activity, which of course increases or decreases complete happiness of the individual/society. The system of Lagrange multiplier is a strongly valuable method in advanced calculus that is applied in this paper with a pair of constraints. This paper also tries to show the economic results of optimization precisely but elaborately.